Analisis Pengaruh Penggunaan Picture Archiving and Communication System (PACS) Terhadap Waktu Tunggu Pelayanan Radiologi - Oktavia, Prameswari; Yoshandi, T. Mohd.; Mutiara, Sherly (TIN: Terapan Informatika Nusantara, 2023)
The waiting time for radiology services is the grace period from the patient in the photo to receiving the results that have been experienced by the radiologist. One that affects the waiting time for radiology services is the use of PACS in radiology. PACS is a system that functions to receive, store, display and distribute radiological medical images. Since 2022, the Radiology service at one of Hospital in Pekanbaru has carried out a digital system, namely the use of PACS on all computers. The use of PACS at one of Hospital in Pekanbaru does not always run efficiently, not infrequently there are several examinations that get the results of doctor expertise/doctor's reading results that are long enough, even exceeding the minimum service standards. The purpose of this study was to determine the effect of using Picture Archiving and Communication System (PACS) on the waiting time for Radiology services. This research is a type of descriptive quantitative research through document studies. This research was conducted at the Radiology Installation one of Hospital in Pekanbaru by taking samples of 300 data for 2021 and 300 data for 2023. From the results of this study, it was found that there was an influence of the use of PACS on Radiology service time seen from the tcount of 4.688 which was greater than the ttable of 1.6474 with a large influence of 4%.